DESIGN OF COLLABORATIVE AND PARTICIPATORY LEARNING MODELS IN MICROTEACHING COURSE - Mitasari, Zuni; Trianawati, Anis (Bio-Lectura : Jurnal Pendidikan Biologi, 2025)
Higher education performance measured using Indikator Kinerja Utama (IKU). The existence of these indicators will accelerate the transformation of higher education so that it is adaptive and globally competitive. IKU 7 where learning activities in the classroom must implement collaborative and participatory learning. The research objective is to develop a microteaching lesson study course model design that accommodates collaborative and participatory learning. This research is development research using a 4D model consisting of the Define, Design, Develop, Disseminate stages. The research results obtained a validity coefficient of 1.0, including the very high validation category, the development of a valid instrument and can be used in data collection. Microteaching lesson study is a model for improving the quality of prospective teachers by implementing three stages of lesson study (plan, do, see) in learning microteaching courses. To accommodate collaborative and participatory learning in microteaching courses, assignment activities are directed using the case method and team-based project.